2016
DOI: 10.1097/tp.0000000000000910
|View full text |Cite
|
Sign up to set email alerts
|

The Dutch Transplantation in Vasculitis (DUTRAVAS) Study

Abstract: In this study in 110 Dutch patients, the recurrence rate of AAGN within 5 years after kidney transplantation appeared slightly higher than in previous reports. Moreover, recurrence of AAGN contributed independently to kidney allograft loss, emphasizing the importance of clinical vigilance, because early treatment might be critical to rescuing the allograft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Previous studies had reported good graft and patient survival in smaller cohorts of renal transplant recipients who had ESRD due to antineutrophil cytoplasmic antibody-associated vasculitis (AAV). 341014…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had reported good graft and patient survival in smaller cohorts of renal transplant recipients who had ESRD due to antineutrophil cytoplasmic antibody-associated vasculitis (AAV). 341014…”
Section: Discussionmentioning
confidence: 99%
“…In the two reported cases of de novo AAV, treatment with steroid and cyclophosphamide or steroid alone led to graft loss after 5 years or significantly impaired graft function at 6 months respectively [ 5 , 6 ]. There are several retrospective case series on the management of disease relapses after transplantation, the largest comprising 13 patients [ 4 , 15 ]. While older reports more commonly quote the use of cyclophosphamide, we found thirteen cases that were treated with rituximab [ 15 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several retrospective case series on the management of disease relapses after transplantation, the largest comprising 13 patients [ 4 , 15 ]. While older reports more commonly quote the use of cyclophosphamide, we found thirteen cases that were treated with rituximab [ 15 21 ]. Twelve of these responded to rituximab-based therapy, although publication bias may exaggerate this apparent efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…One cohort study, in particular, demonstrated that patient and transplant survival was better in AAV compared to nondiabetic patients [45]. Various single and multi-center cohort studies have evaluated the outcomes of renal transplantation in patients with AAV [8,11,12,19,22,[46][47][48][49][50][51] and have shown that the rate of patient and transplant survival in AAV is equal and comparable to control nondiabetic patients. The five-year posttransplant patient survival ranges between 77% and 96%, and the five-year graft survival is between 60% and 100%.…”
Section: Outcomes Of Kidney Transplantation In Aavmentioning
confidence: 99%
“…For this reason, despite the recurring nature of this disease, renal transplantation should be offered once they are eligible for patients with ESKD secondary to AAV. At the same time, the literature detailing the recurrence of AAV among kidney allograft recipients is equally extensive and compelling [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%